Ethnic Identity and Cultural Resilience in Banten and Pattani: Historical Legacies, State Policies, and Globalisation - Kheryadi, Kheryadi; Chorbwhan, Rungroj (Indigenous Southeast Asian and Ethnic Studies, 2025)
This study compares the preservation and adaptation of ethnic identities in Banten (Indonesia) and Pattani (Thailand), with particular attention to the effects of globalisation, state policies, and political conflict. It examines how historical legacies, cultural practices, education, and socio-economic interactions have shaped identity in both regions. In Banten, the Sultanate era (seventeenth to nineteenth centuries) created a cosmopolitan society through trade and Islamic learning, where Javanese, Sundanese, Arab, Persian, and Chinese communities coexisted. Today, Banten continues to integrate traditional practices with modern technologies, with education playing a central role in sustaining heritage. Pattani, by contrast, faces ongoing struggles of cultural preservation in a politically contested environment. The Malay-Muslim community demonstrates resilience through the preservation of language, religious education, and traditional arts, despite tensions with the Thai state. The findings reveal both similarities and divergences, underscoring the need for context-sensitive strategies to safeguard ethnic identities and foster coexistence in diverse societies.